High-dimensional quantum key distribution implemented with biphotons - Comfort Sekga; Mhlambululi Mafu; Makhamisa Senekane (Scientific Reports, 2023)
Abstract We present a high-dimensional measurement device-independent (MDI) quantum key distribution (QKD) protocol employing biphotons to encode information. We exploit the biphotons as qutrits to improve the tolerance to error rate. Qutrits have a larger quantum system; hence they carry more bits of classical information and have improved robustness against eavesdropping compared to qubits. Notably, our proposed protocol is independent of measurement devices, thus eliminating the possibility of side-channel attacks. Also, we employ the finite key analysis approach to study the performance of our proposed protocol under realistic conditions where finite resources are used. Furthermore, we simulated the secret key rate for the proposed protocol in terms of the transmission distance for different fixed amounts of signals. The results prove that this protocol achieves a considerable secret key rate for a moderate transmission distance of 90 km by using $$10^{16}$$ 10 16 signals. Moreover, the expected secret key rate was simulated to examine our protocol’s performance at various intrinsic error rate values, $$Q=(0.3%,0.6%,1%)$$ Q = ( 0.3 % , 0.6 % , 1 % ) caused by misalignment and instability due to the optical system. These results show that reasonable key rates are achieved with a minimum data size of about $$10^{14}$$ 10 14 signals which are realizable with the current technology. Thus, implementing MDI-QKD using finite resources while allowing intrinsic errors due to the optical system makes a giant step forward toward realizing practical QKD implementations.